ChemInform Abstract: One‐Step Synthesis of Xanthones Catalyzed by a Highly Efficient Copper‐Based Magnetically Recoverable Nanocatalyst. Issue 47 (6th November 2014) - Menendez, Cintia A.; Nador, Fabiana; Radivoy, Gabriel; Gerbino, Dario C.
Abstract A novel and magnetically recoverable catalyst consisting of copper nanoparticles on nanosized silica coated maghemite is utilized for the convenient synthesis of xanthones.